DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Thioredoxins are involved in the activation of the PMK1 MAP kinase pathway during appressorium penetration and invasive growth in Magnaporthe oryzae - Shijie Zhang; Cong Jiang; Qiang Zhang; Linlu Qi; Chaohui Li; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary In Magnaporthe oryzae , the Mst11‐Mst7‐Pmk1 MAP kinase pathway is essential for appressorium formation and invasive growth. To determine their roles in Pmk1 activation and plant infection, we characterized the two thioredoxin genes, TRX1 and TRX2 , in M. oryzae . Whereas the Δ trx1 mutants had no detectable phenotypes, deletion of TRX2 caused pleiotropic defects in growth, conidiation, light sensing, responses to stresses and plant infection progresses. The Δ trx1 Δ trx2 double mutant had more severe defects than the Δ trx2 mutant and was non‐pathogenic in infection assays. The Δ trx2 and Δ trx1 Δ trx2 mutant rarely formed appressoria on hyphal tips and were defective in invasive growth after penetration. Pmk1 phosphorylation was barely detectable in the Δ trx2 and Δ trx1 Δ trx2 mutants. Deletion of TRX2 affected proper folding or intra‐/inter‐molecular interaction of Mst7 and expression of the dominant active MST7 allele partially rescued the defects of the Δ trx1 Δ trx2 mutant. Furthermore, Cys305 is important for Mst7 function and Trx2 directly interacts with Mst7 in co‐IP assays. Our data indicated that thioredoxins play important roles in intra‐cellular ROS signalling and pathogenesis in M. oryzae . As the predominant thioredoxin gene, TRX2 may regulate the activation of Pmk1 MAPK via its effects on Mst7.

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Composition of phosphorus in wetland soils determined by SMT and solution 31P-NMR analyses - Wenqiang Zhang; Xin Jin; Yuekui Ding; Xiaolei Zhu; Nan Rong; Jie Li; Baoqing Shan (Environmental Science and Pollution Research, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Phosphorus speciation of sediments from lakes of different tropic status in Eastern China - Wenqiang Zhang; Nan Rong; Xin Jin; Jie Li; Yuekui Ding; Xiaolei Zhu; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Anthropogenic footprint of climate change in the June 2013 northern India flood - Changrae Cho; Rong Li; S.-Y. Wang; Jin-Ho Yoon; Robert R. Gillies (Climate Dynamics, 2016)